Antiretroviral therapy-treated HIV-infected adults with coronary artery disease are characterized by a distinctive regulatory T-cell signature. (1st June 2021) - Rothan, Céline; Yero, Alexis; Shi, Tao; Farnos, Omar; Chartrand-Lefebvre, Carl; El-Far, Mohamed; Costiniuk, Cecilia T.; Tsoukas, Christos; Tremblay, Cécile; Durand, Madeleine; Jenabian, Mohammad-Ali
Abstract : Background: Despite the success of antiretroviral therapy (ART) to control viral replication, people living with HIV (PWH) have high levels of chronic systemic inflammation and immune dysregulation which drives accelerated co-morbidities including coronary artery disease (CAD). Regulatory T cells (Tregs) and ectonucleotidases CD39/CD73 are known to be athero-protective via their immunosuppressive and anti-inflammatory functions. Design: We assessed the dynamics of Treg subsets in ART-treated PWH with or without CAD vs. HIV-uninfected individuals. Methods: Blood specimens were obtained from 142 participants including ART-treated HIV-infected adults with ( n  = 43) or without CAD ( n  = 41), as well as HIV-uninfected controls with ( n  = 31) or without CAD ( n  = 27). CAD was determined by the presence of atherosclerotic features on computed tomography angiography of the coronary arteries performed on all study participants. Treg subsets frequencies were assessed by flow cytometry. Results: Regardless of statin treatment or ART regimen, HIV + CAD + individuals had the highest total Treg frequencies and increased thymic generation and output of Tregs (Helios/CD31 expression), while athero-protective CD39 + /CD73 + Tregs were significantly depleted in this group. Tregs from PWH had higher expression of CCR6/CXCR3 than uninfected individuals regardless of CAD, while in HIV + CAD + individuals Tregs expressed the highest levels of CCR4, which limits their maintenance. The lowest levels of CD4 + and CD8 + T-cell immune activation has been observed in HIV + CAD + within study groups. Conclusion: ART-treated PWH with diagnosed CAD are characterized by profound alterations in populations of anti-inflammatory and athero-protective Treg subsets. These changes may contribute to atherosclerotic plaque formation and progression during chronic HIV infection in the ART era. Abstract : Supplemental Digital Content is available in the text